THE INVESTIGATION OF DANGER RISK BY OPERATE THE MAIN OIL PIPELINE - Возняк, Мирослав Петрович; Возняк, Лідія Володимирівна; Кривенко, Галина Мирославівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The diagram of investigation pipeline for forecast the risk is given. The distribution of pressure across the length of the pipeline gives the forecast volume rate of oil. Computers model the flow of oil through the orifices gives the direction and covered of oil area. Calculate of danger risk is given.